Zooplankton Community Structure in Arctic Ponds: Shifts Related to Pond Size - O'Brien, W. John; Luecke, Chris (ARCTIC, 2011)
A multi-year experiment in which zooplankton species were manipulated in 12 ponds indicated that the presence of the carnivorous copepod Heterocope septentrionalis eliminated Daphnia pulex whenever H. septentrionalis became established. In contrast, the congener D. middendorffiana was able to persist only in ponds where H. septentrionalis became established. The fact that Daphnia middendorffiana could not successfully colonize ponds that did not contain H. septentrionalis indicates that this predator was necessary for D. middendorffiana to thrive. These results suggest that D. pulex is able to outcompete D. middendorffiana when H. septentrionalis is absent. Pond size was a key determinant of colonization success, in that H. septentrionalis and D. middendorffiana were able to persist only in ponds with volumes greater than 10 m3. Results of these investigations support the pattern of zooplankton community composition observed in ponds in the western Nearctic and provide insight into the mechanisms responsible for these observations. Une expérience échelonnée sur plusieurs années dans le cadre de laquelle les espèces de zooplancton de 12 étangs ont été manipulées a permis de déterminer que la présence du copépode carnivore Heterocope septentrionalis a éliminé le Daphnia pulex lorsque le H. septentrionalis s’était établi. En revanche, le congénère D. middendorffiana n’a pu persister que dans les étangs où H. septentrionalis s’était établi. Le fait que Daphnia middendorffiana n’a pas réussi à coloniser les étangs qui ne renfermaient pas H. septentrionalis indique que la présence de ce prédateur s’avérait nécessaire pour que D. middendorffiana puisse prospérer. Ces résultats laissent croire que D. pulex est capable de déplacer D. middendorffiana lorsque H. septentrionalis est absent. La taille de l’étang représentait un déterminant-clé en matière de réussite de la colonisation, en ce sens que H. septentrionalis et D. middendorffiana n’ont réussi à persister que dans les étangs dont le volume était supérieur à 10 ...